Indonesia Economic Quarterly, October 2015 : In Times of Global Volatility - World Bank (World Bank, Washington, DC, 2018)
The Indonesia Economic Quarterly (IEQ) has two main aims. First, it reports on the key developments over the past three months in Indonesia’s economy, and places these in a longerterm and global context. Based on these developments, and on policy changes over the period, the IEQ regularly updates the outlook for Indonesia’s economy and social welfare. Second, the IEQ provides a more in-depth examination of selected economic and policy issues, and analysis of Indonesia’s medium-term development challenges. It is intended for a wide audience, including policymakers, business leaders, financial market participants, and the community of analysts and professionals engaged in Indonesia’s evolving economy. This quarterly report covers the economic growth of Indonesia as in October 2015. Indonesia’s growth moderation has continued and an uncertain external environment has further limited the room for both monetary and fiscal stimulus and has turned the government’s focus to structural and fiscal reforms to raise investor confidence in Indonesia. The government recognizes the need to improve business confidence and the investment climate in order to enhance Indonesia’s potential growth rate and has taken several important steps in this direction. In addition to the policy packages, the draft 2016 State Budget signals the objective of further improving the composition of public expenditures by strengthening social programs and by redirecting spending from energy subsidies to infrastructure development. Timely and effective implementation of these reforms will contribute to returning to a higher sustainable pace of growth.